Fabrication and Characterization of Ozenoxacin and Curcumin Loaded Electrospun Nanofibre Membrane for Full Thickness Wound Healing: In vitro Assessments - Vasanth, A; Subashini, P; Jerad Suresh, A; Mubeena, S; Punnoose, Alan Mathew; Maanvizhi, Saba (Asian Journal of Biological and Life Sciences)
Aim/Background: The development of advanced wound care solutions is critical due to the significant global impact of chronic and acute wounds. This study focuses on fabrication of a biodegradable and biocompatible nanofibre scaffold for enhanced wound healing, combining antimicrobial and anti-inflammatory properties. Materials and Methods: The present research work was carried out during December 2023 to July 2024. Nanofibres were developed using electrospinning with a Polyvinyl Alcohol (PVA) and gelatin blend, incorporating with ozenoxacin and curcumin as therapeutic agents. Results: The viscosity of the polymer solution prior to electrospinning was found to be at 39.48 Pa.s, ensuring optimal fibre formation. Scanning Electron Microscopy confirmed uniform fibres with diameters between 50-114 nm. Fourier-Transform Infrared Spectroscopy (FT-IR) and X-ray Diffraction (XRD) analyses verified that there is no chemical interaction and further crystalline nature of the incorporated agents respectively. In vitro release studies demonstrated a sustained release profile of both ozenoxacin and curcumin over 24 hr, indicating prolonged therapeutic potential. Conclusion: This dual-functional scaffold addresses infection control and inflammation reduction, offering a comprehensive approach to wound management and making it a promising candidate for advanced wound care applications.
Keywords: Electrospinning; Nanofibres; Ozenoxacin; Wound healing